Ultrasound-guided posterior quadratus lumborum block can reduce postoperative opioid consumption and promote rapid recovery in patients undergoing sutureless laparoscopic partial nephrectomy: A triple-blind, randomized, controlled study - Zhu, Youzhuang; Li, Zhichao; Qin, Shangyuan; Xu, Hao; He, Jianshuai; Sheng, Fang; Zhao, Qin; Kang, Yihan; Gao, Xin; Li, Si; Chai, Jun; Chen, Lina; et al. (Frontiers in Oncology, 2022)
Purpose We hypothesized that posterior quadratus lumborum block would reduce postoperative opioid consumption and improve the quality of recovery in patients undergoing sutureless laparoscopic partial nephrectomy. Materials and methods The study included 60 patients, ages 18−65 with American Society of Anesthesiologists scores of I-II scheduled for elective sutureless laparoscopic partial nephrectomy. Before general anesthesia, 60 participating patients were randomly allocated to receive a 30-ml injection posterior to the quadratus lumborum muscle with either 0.375% ropivacaine (n = 30) or normal saline (n = 30). The primary outcomes included cumulative opioid consumption within 12 h postoperatively and quality of postoperative recovery at 48 h. Secondary outcomes included the Numerical Rating Scale (NRS), opioid consumption by period, first time to press the analgesic pump, number of patients needing rescue analgesia, blood glucose and cortisol concentrations, early postoperative recovery indicators, and adverse events. Results There were 48 patients included in the final analysis. The intervention group had lower cumulative consumption of sufentanil within 12 h postoperatively and higher quality of postoperative recovery scores at 48 h postoperatively compared with the control group (p < 0.001). The NRS at resting and movement of the intervention group was lower at 0 h, 6 h, and 12 h after surgery than in the control group (p < 0.05). At prespecified intervals (0 to 2 h, 2 to 6 h, 6 to 12 h, 12 to 24 h, and 24 to 48 h) after surgery, the intervention group had lower consumption of sufentanil compared with the control group (p < 0.05). The intervention group took longer to press the analgesic pump for the first time within 48 h after surgery compared with the control group (p < 0.001). The postoperative blood glucose and cortisol concentrations in the intervention group were lower than in the control group (p < 0.05). The times to first excretion, ambulation, and discharge were shorter in the intervention group compared with the control group (p < 0.05). There was no significant difference in adverse events between the two groups. Conclusions Our trial demonstrated that patients who received posterior quadratus lumborum block had significantly lower opioid consumption within 12 h postoperatively and had a better quality of recovery at 48 h postoperatively. Therefore, we recommend posterior quadratus lumborum block as an option for postoperative analgesia in patients undergoing sutureless laparoscopic partial nephrectomy. Trial Registration http://www.chictr.org.cn, identifier ChiCTR2100053439.